Cardiovascular and Autonomic Dysfunction in Murine Ligature-Induced Periodontitis - Ribeiro, Aline Barbosa (Sci Rep, 2020)
The present study examined the hemodynamics [arterial pressure (AP), AP variability (APV), heart rate (HR), and heart rate variability (HRV)], cardiac function (echocardiographycally), and myocardial inflammation in Balb/c mice submitted to Periodontitis, through the ligation of the left first molar, or Sham surgical procedure. The first protocol indicated that the AP was similar (136 ± 2 vs. 132 ± 3 mmHg in Sham), while the HR was higher in mice with Periodontitis (475 ± 20 vs. 412 ± 18 bpm in Sham), compared to their Sham counterparts. The APV was higher in mice with Periodontitis when evaluated in the time domain (4.5 ± 0.3 vs. 3.4 ± 0.2 mmHg in Sham), frequency domain (power of the LF band of systolic AP), or through symbolic analysis (patterns 0V + 1V), indicating a sympathetic overactivity. The HRV was similar in the mice with Periodontitis, as compared to their Sham counterparts. In the second protocol, the mice with Periodontitis showed decreased cardiac output (10 ± 0.8 vs. 15 ± 1.4 mL/min in Sham) and ejection fraction (37 ± 3 vs. 47 ± 2% in Sham) associated with increased myocardial cytokines (Interleukin-17, Interleukin-6, and Interleukin-4). This study shows that experimental Periodontitis caused cardiac dysfunction, increased heart cytokines, and sympathetic overactivity, in line with epidemiological studies indicating an increased risk of cardiovascular events in clinical Periodontitis.